Parameters of biochemical serum test of pigs in sarcosporidiosis - Seksenova, D.U.; Esimov, B.K.; Ibragimova, Z.A. (KSU Publ., 2020)
Sarcocystoses (sarcosporidioses, sarcocystoses) are invasive diseases caused by protozoa — coccidia of the genus Sarcocystis, the family Sarcocystidae. The main damage the disease causes livestock. Being localized in the muscles and heart of intermediate hosts (cattle and small cattle, pigs) cause exhaustion, anemia, decreased productivity and even death. In 1843, the German scientist Miescher first described characteristic intramuscular formations in the skeletal muscles of a domestic mouse, believing that these were clusters of parasites of unknown nature. Subsequently, similar formations in the muscles of other animals began to be described under different names: “Misher's bags”, “Rhine bodies”, “psorospermia” (ie scabies sperm). It was only in 1882 that Lankester began to call them meat cysts, or sarcocists, and proposed for their designation the corresponding generic name — Sarcocystis. A change in the level of iron, zinc, total and ionizing calcium in pig blood was observed during the clinical symptoms of sarcosporidiosis, when the disease is transmitted to the muscle. The article analyzes the changes in minerals and the activity of enzymes in the blood.
Саркоспоридиоз кезінде шошқаның қан сарысуындағы биохимиялық көрсеткіштер
Биохимические показатели в сыворотке крови свиней при саркоспоридиозе
Keywords: sarkosporidiosis; hyperthermi; hypercupremia; hypercalcemia; enzymes; dynamics; sarcocystosis; blood serum